UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN SIRSAK (Annona muricata L) PADA TIKUS PUTIH (Rattus norvegicus) DIABETES MELITUS YANG DIINDUKSI ALOKSAN DENGAN PARAMETER MALONDIALDEHID (MDA) - Safriani Rahman; Rachmat Kosman; Inda Rahmaniar (As-Syifaa Jurnal Farmasi, 2014)
Hyperglycemia in Diabetes can caused the excessive production of Reactive Oxygen Species (ROS) in the body that will causes oxidative  stress that tissue damage. Oxidative stress can indicated by increasing MDA levels. This research aims to know and determine the concentration ethanol extract of soursop leaves that have antioxidant activity to MDA levels in diabetic rats. 9 white rats were divided into 3 groups. All rats were induced by alloxan 110mg/Kg.BB intraperitoneally. Group I was administered with Na.CMC as a negative control, group II and III were administered with ethanol extract of soursop leaves 2,5% and 5%. Administration were given orally for 12 days orally. Examination of blood glucose and MDA levels conducted before and after the administration. MDA Assay performed with TBA method was based on reaction of MDA-TBA as measured on a spectrophotometer 532 nm wavelength. The results were analysized statistically by using randomized block design (RBD) method. Based on the research has been done, it was showed that the ethanol extract of soursop leaves can lower blood glucose levels of diabetic rats and extract with concentration of 5% has potential as an antioxidant activity that can reduce MDA levels in diabetic rat.